PEMANFAATAN KOMPOS BERBAHAN BAKU AMPAS TEBU (Saccharum sp.) DENGAN BIOAKTIVATOR Trichoderma spp. SEBAGAI MEDIA TUMBUH SEMAI Acacia crassicarpa - Rahimah '; M. Mardhiansyah '; Defri ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Bagasse is a waste which is usually dumped in open dumping without any further processing, so it will cause an enviromental disturbance. It is important to apply a technology to overcome the waste by using the recycle of solid waste into a use value of compost product. Top soil has been hard to find, because it is used continously in long time or has been eroded which cause the decreasing of avalaiblity. Alternative to avoid the decreasing of soil media quality, so the use of compost is predicted to increase the supply of soil nutrient. The purpose of this research is to determine the effect  of composting formulated bagasse for Acacia crassicarpa seedlings in top soil medium and to determine the best dose for seedling growth Acacia crassicarpa. This research uses a completely randomize design method which consist of 5 treatments, 4 replications, and 5 units of the plant as a research unit. P0 = without composting  formulated bagasse ; P1 = 25 g/polybag ; P2= 50 g/polybag ; P3 = 75 g/polybag ; p4 = 100 g/polybag. The result of this research indicates that  the composting formulated bagasse with 100 g/polybag dose is the best treatment in the parameter observations, the high increasing (36.45 cm), the diameter increasing (0.37 mm), the seedling dry weight (11.93 g), and the ratio of the root crown (6.40) for seedling Acacia crassicarpa in top soil medium. Keyword: : Compost bagasse, Trichoderma spp, Acacia crassicarpa.